Modelling and controlling of multilevel converters for smart grid applications - Dzulfaqar Shah Muhamad (2018)
The modular multilevel converter (MMC) has been a subject of increasing interests for medium and high-power conversions in smart grids application. There have been several advancements of MMC over the last few years, however, MMC presents new challenges mainly due to the increasing complexity of controlling power circuits and more available switching states. The objectives are to provide techniques for the following control objectives which are voltage capacitor balancing method, output power control and voltage ripple reduction. Capacitor voltage fluctuation is still an issue in MMC, hence, capacitor voltage balancing control is needed to maintain the capacitor voltages using a voltage sorting algorithm and PD-PWM. The output power control uses a resonant controller to track the output current. It is noted that resonant controller is only used for single-phased MMC. In a three-phased system, a Direct-Quadrature-Zero (D-Q) or Space Vector transformation will be chosen to simplify the complexity of the control loops. The Capacitor Voltage Ripple depends on the upper and lower SM capacitor currents. Moreover, they also depend on the upper and lower modulation signals and the upper and lower arm currents.